The provisional application of treaties by the Peruvian State - Loayza Juárez, Jorge (2022)
Currently, only treaties concluded in compliance with a certain formality and in force are part of the national legal system. The existing domestic rules do not provide for the possibility of provisional application of a treaty, and even less regulate the manner in which the State gives its consent to provisionally apply a treaty. However, in practice, the Peruvian State has improperly provisionally applied two treaties. Therefore, by means of this article, we propose to make a normative modification that allows the use of provisional application.